AN ANALYSIS OF WORLDWIDE FACTORS AND INFLUENCES AFFECTING WORK SATISFACTION IN NURSES - Dalal Nukhaylan Almutiri; Abdulaziz Abdulmajeed Alheliao; Yazeed Salem Alshuwayman; Jwaher Abdurabuh Alsaleem; Bayan Ali Alkhalifah; Ahmed Ali Alhamadah; Nourah Naif Algethmi; Bader Hamad Alhamdani; Aishe Saadi Alshmmrey; Salma Hulel Alotaibi; Abdullah Salem Musayyab Alharbi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The large body of research on nurses’ job satisfaction and the variables affecting it is examined in this study. High turnover and widespread shortages of nurses have become worldwide issues. It’s critical to comprehend nurses’ job happiness because it impacts hospital care quality and influences nurses’ decisions to remain in or leave the field. There are numerous contributing aspects to the complex phenomena of job happiness. Numerous reasons of happiness and discontent have been identified by researchers, including: Work environment: This includes physical workspace, relationships with managers and coworkers, workload, and autonomy. Compensation and benefits: pay, opportunities for advancement, and job security are all significant factors. Recognition: Getting recognition from superiors and coworkers is a major source of motivation. The nature of the work itself: Nurses who find their work interesting and challenging generally have higher levels of job satisfaction. Research from a variety of nations has demonstrated the importance of these factors for nurses globally